If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 4x = 5x + -12 Reorder the terms: 7 + 4x = -12 + 5x Solving 7 + 4x = -12 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 7 + 4x + -5x = -12 + 5x + -5x Combine like terms: 4x + -5x = -1x 7 + -1x = -12 + 5x + -5x Combine like terms: 5x + -5x = 0 7 + -1x = -12 + 0 7 + -1x = -12 Add '-7' to each side of the equation. 7 + -7 + -1x = -12 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = -12 + -7 -1x = -12 + -7 Combine like terms: -12 + -7 = -19 -1x = -19 Divide each side by '-1'. x = 19 Simplifying x = 19
| 15+4(m-2)=21 | | 4(s+7)-8=10(s-4) | | -5b+24=-1 | | 2+3(x+1)=17 | | 10-4x=-x | | 16-3y+4y=27 | | 7c+3-5c=15 | | 3x+8=5x+9 | | -4f+1=13 | | 3x+7=2x+4 | | 125x=25x+1 | | 5m-12-3m=2m+8 | | -9d-1=17 | | 26x+2=18x+48x+6 | | 2(x+4)+36=-3x | | -2x-4=8 | | 5X+12=8X-12 | | 2a+5b=10a+14b | | -12x+3=51 | | -4x-20+9x=-5 | | 5*(x+3)=3*(2x-1) | | 3G-49=-7 | | 11x-13-27-13x=0 | | -12x-3=-51 | | 11xcv+456-35yU=o | | 7+4x=10x-11 | | 15a-54=-9 | | 5x+7=2x+4 | | -56=20-(-e) | | 11x-24=-2 | | x-(-74)=-22 | | 8-2y=2y-2-y |